Characteristics Analysis of Bokhasi Fertilizer Made from Spent Coffee Grounds (SCG) - Nur Viya Lisma; Asiah MD; Iswadi Iswadi; Samingan Samingan; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Spent Coffee Ground (SCG) is a biowaste generated through the process of serving coffee brewed either manually or using an instant coffee processing machine. According to previous researches, SCG has a lot of organic compounds so that it can be used as raw material for solid or liquid organic fertilizer. The purpose of this study was to determine the biological characteristics (types of fungi and bacteria) and the suitability of the chemical content (levels of C, N, P, K, C / N ratio), water content and pH of bokashi SCG fertilizer with SNI 7763:2018. This research is an descriptive research with quantitative and qualitative approaches. The analysis conducted on Bokashi fertilizer is microbial type analysis, water content analysis, pH test, FTIR test and UV-Vis. The parameters of this study are the types of microbes, levels of C, N, P, K, C / N ratio, moisture content and fertilizer pH. Based on the results of the study it can be concluded that SCG bokashi fertilizer is an organic fertilizer containing 4 types of mushrooms namely Aspergillus sp., Cladorrhinum sp., Penicillium sp., Rhizopus sp., And 4 isolate types of bacteriawith a C content of 29.71%; N level of 3.65%; P level 0.30%; K content of 0.38%; C / N ratio of 8.14; 10% moisture content; and pH 6.7 which is in accordance with SNI 7763: 2018. Keywords:SCG, bokashi, microbes, biofertilizerABSTRAKSpent Coffee Ground (SCG) merupakan limbah yang dihasilkan melalui proses penyajian kopi yang diseduh baik secara manual maupun menggunakan mesin pengolah biji kopi instan. Menurut penelitian terdahulu, SCG memiliki banyak kandungan senyawa organik sehingga dapat dimanfaatkan sebagai bahan baku pupuk organik padat maupun cair. Tujuan penelitian ini adalah untuk mengetahui karakteristik biologi (jenis jamur dan bakteri) dan kesesuaian kandungan kimia (kadar C, N, P, K, rasio C/N), kadar air dan pH pupuk bokashi SCG dengan SNI 7763:2018. Penelitian ini merupakan penelitian eksperimental dengan pendekatan kuantitatif dan kualitatif. Analisis yang dilakukan pada pupuk bokashi yaitu analisis jenis mikroba, analisis kadar air, uji pH, uji FTIR dan UV-Vis. Parameter penelitian ini yaitu jenis mikroba, kadar C, N, P, K, rasio C/N, kadar air dan pH pupuk. Berdasarkan hasil penelitian dapat disimpulkan bahwa pupuk bokashi SCG merupakan pupuk organik yang mengandung 4 jenis jamur yaitu Aspergillus sp., Cladorrhinum sp., Penicillium sp., Rhizopus sp., dan 4 isolat, dengan kadar C 29,71%; kadar N 3,65%; kadar P 0,30%; kadar K 0,38%; rasio C/N 8,14; kadar air 10%; dan pH 6,7 sesuai dengan SNI 7763:2018. Kata kunci: SCG, bokashi, mikroba, pupuk organik